No preference in female sika deer for conspecific over heterospecific male sexual calls in a mate choice context. (6th March 2014) - Wyman, M. T.; Locatelli, Y.; Charlton, B. D.; Reby, D.
Abstract Mating signals can be used both in contexts of species recognition and mate quality assessment. This study examines species recognition abilities in oestrous females presented with male mating calls from both conspecifics and closely related allopatric heterospecifics. Red deer and sika deer are naturally allopatric polygynous species capable of hybridization during sympatry. Male mating calls are sexually selected and differ greatly between species. Previous work indicated that most but not all oestrous red deer hinds prefer male mating calls from conspecifics over heterospecific sika deer. Using two‐speaker playback experiments, we extend this examination by measuring the preference responses of oestrous sika deer hinds to these stimuli. We predicted that oestrous sika deer hinds will show little flexibility in behavioural responses and prefer conspecific calls over heterospecific calls, similar to those of red deer hinds. In contrast, sika deer hinds showed high levels of flexibility and no difference in overall preference behaviours, suggesting that vocal behaviour does not provide a solid barrier to hybridization in this species. The asymmetry in heterospecific preference responses between these species is discussed in relation to possible causation and hybridization patterns observed in free‐ranging populations.